Constructing a 2D/2D heterojunction of MoSe2/ZnIn2S4 nanosheets for enhanced photocatalytic hydrogen evolution. Issue 13 (23rd March 2021) - Feng, Ting; Zhao, Kaili; Li, Haiyan; Wang, Wei; Dong, Bohua; Cao, Lixin
Abstract : 2D/2D MoSe2 /ZnIn2 S4 heterojunctions exhibit high photocatalytic activity owing to MoSe2 as a cocatalyst, which provides more active sites, reducing the overpotential and the activation energy for water reduction. Abstract : The low separation efficiency and high recombination of photogenerated charge carriers are the main challenges in the development of effective photocatalytic materials. The construction of two-dimensional (2D) nanosheet heterostructures with a co-catalyst would accelerate the photogenerated charge transfer and increase the number of active sites for H2 evolution, which may be an effective strategy to improve charge separation efficiency and reduce recombination. In this research, novel 2D/2D MoSe2 /ZnIn2 S4 complex heterojunctions have been successfully synthesized by a secondary hydrothermal method. 2D ZnIn2 S4 nanosheets were firstly prepared and then 2D MoSe2 nanosheets were formed on the ZnIn2 S4 . As a cocatalyst, the 2D MoSe2 nanosheets could provide abundant active sites reducing the overpotential and the activation energy for water reduction. By synergic effects, the 2D/2D heterojunction formed between MoSe2 and ZnIn2 S4 can provide a large and intimate contact area, which accelerates the photogenerated charge separation and transfer resulting in high photocatalytic activity. It has been demonstrated that the H2 evolution rate using 10%MoSe2 /ZnIn2 S4 as the catalyst is 10 times higher than that using ZnIn2 S4 alone as the catalyst, which is 1226 μmol g −1 h −1 and 116 μmol g −1 h −1, respectively, in water splitting under visible light irradiation. This work provides more insights into the rational design and synthesis of 2D heterostructures by using 2D materials as co-catalysts.